2022
DOI: 10.1007/s11356-022-18666-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of economic freedom and clean energy in environmental sustainability: implication for the G-20 economies

Abstract: With the increasing challenge of attaining sustainable balance in socioeconomic-ecosystem activities, the aspects of the global goals are continously being harnesed in order to ensure a sustainable interaction. As an alliance of the United Nations, the G-20 member countries have not only committed to attaining the Sustainable Development Goals 2030, the alliance body has further fostered frameworks that are targeted at advancing global economic and environmental sustainability. Within this context, the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 38 publications
3
36
1
Order By: Relevance
“…In the related empirical literature, Adesina and Mwamba [35] revealed a negative effect of the trade freedom index on CO 2 emissions in 24 African economies. Alola et al [40] reached similar findings for G-20 countries. Therefore, our findings and the related empirical literature point out that international trade freedom is a significant determinant of CO 2 emissions for developing and developed countries.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…In the related empirical literature, Adesina and Mwamba [35] revealed a negative effect of the trade freedom index on CO 2 emissions in 24 African economies. Alola et al [40] reached similar findings for G-20 countries. Therefore, our findings and the related empirical literature point out that international trade freedom is a significant determinant of CO 2 emissions for developing and developed countries.…”
Section: Resultssupporting
confidence: 53%
“…The limited empirical literature on the nexus between economic freedom and the environment has generally utilized the regression approach and found mixed findings. Odugbesan et al [14], Cheon et al [34], Adesina and Mwamba [35], Bjørnskov [36], and Jain and Kaur [37] discovered a negative influence of economic freedom indicators on CO 2 emissions, but Wood and Herzog [38], Rapsikevicius et al [39], Chen [24], and Alola et al [40] have revealed mixed findings on the influence of economic freedom indicators on CO 2 emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Fossil fuels dominate energy investments. As a result, it is critical to move financial resources away from nonrenewable energy sources and toward sources that reduce carbon emissions ( Alola et al, 2022 ). Investments in green bonds offer a wide range of benefits in addition to their environmental benefits.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since it first implemented its policy of reform and opening to the outside world in 1978, China, one of the largest developing countries, has gone through a period of rapid change. China's GDP grew at the rate of 9.7 percent per year over the course of the last 20 years, propelling the country into the top 10 list of the world's largest economies ( 8 ). However, this rapid expansion has resulted in the depletion of significant amounts of resources and an increase in the amount of pollution produced.…”
Section: Introductionmentioning
confidence: 99%